2012
DOI: 10.1063/1.4729588
|View full text |Cite
|
Sign up to set email alerts
|

Determination of in-depth damaged profile by Raman line scan in a pre-cut He2+ irradiated UO2

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
76
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 18 publications
8
76
1
Order By: Relevance
“…14) and UO 2 (ref. 43), while Al 2 O 3 has been shown to undergo both reduction 44 and anion-selective defect accumulation 45 . Anion segregation, accompanied by chemical reduction, has also been observed in Al 2 O 3 irradiated with an ultrafast laser 46 , which, similar to high-energy heavy ions, deposits energy in a material via electronic excitation.…”
Section: Resultsmentioning
confidence: 99%
“…14) and UO 2 (ref. 43), while Al 2 O 3 has been shown to undergo both reduction 44 and anion-selective defect accumulation 45 . Anion segregation, accompanied by chemical reduction, has also been observed in Al 2 O 3 irradiated with an ultrafast laser 46 , which, similar to high-energy heavy ions, deposits energy in a material via electronic excitation.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing complementary analytical techniques described in this article (RBS and XRD) and electron microscopy techniques [17,18], Raman spectroscopy studies have revealed ion-induced structural modifications (defects, distortion of bonds, fluorite phase transformation and amorphization) in binary oxides, such as zirconia [40], ceria and urania [41], and more complex oxides, such as pyrochlores [39,43]. In nanocrystalline monoclinic ZrO 2 thin films, Raman spectroscopy has been utilized to characterize the structural changes and phase evolution as a function of increasing fluence induced by the swift heavy ion irradiation [40].…”
Section: Raman Spectroscopymentioning
confidence: 98%
“…As a result of the interaction of the laser light with molecular vibrations, phonons or other excitations, the energy of the laser photons can be shifted up or down, which then contains information about the vibrational modes in the sample. Raman spectroscopy has been increasingly applied for the structural characterization of ion-beam modified materials, such as in carbides [36][37][38] and oxides [39][40][41][42]. More recently, micro-Raman spectroscopy has been used to characterize the damage created over the entire ion range [36,41,42] to provide new information on quantification of the damage and structure modification as a function of depth, and on enlightenment of possible synergistic effects due to both nuclear and electronic energy deposition to the materials [31].…”
Section: Raman Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations